STUDI ETNOBOTANI EKONOMI TANAMAN SAGU (Methroxylon sagu) PADA MASYARAKAT ADAT LUWU DI KABUPATEN LUWU SULAWESI SELATAN - Naima Haruna; Syamsuri Syamsuri; Hasria Alang (Universitas Lancang Kuning, 2022)
Methroxylon sago, a plant that is widely used in daily life, for example by the indigenous people of Luwu. The research about the importance of these plants for the indigenous people of Luwu has never been carried out. The aimed of study to document local knowledge in the form of the importance of using sago by the Luwu indigenous people in their daily lives. The sampling method used in this research is exploration and observation. Determination of respondents or informants of this research using purpose sampling. Collecting data using Participatory Rural Appraisal (PRA) through interviews. The results showed that the indigenous people of Luwu used sago fronds as materials for making toys, rafts, household utensils, house walls, traditional rituals and glue. Sago leaves are used as building materials, sago starch is used as food, sago stems are used as fuel and house floors. So it can be concluded that sago plants have an important meaning and economic value in daily life by the Luwu indigenous people.